NEW
New Website Launch
Experience the best way to solve previous year questions with mock tests (very detailed analysis), bookmark your favourite questions, practice etc...
1

WB JEE 2010

MCQ (Single Correct Answer)

If $$\alpha$$, $$\beta$$ be the roots of the quadratic equation x2 + x + 1 = 0 then the equation whose roots are $$\alpha$$19, $$\beta$$7 is

A
$${x^2} - x + 1 = 0$$
B
$${x^2} - x - 1 = 0$$
C
$${x^2} + x - 1 = 0$$
D
$${x^2} + x + 1 = 0$$

Explanation

$$\because$$ $$\alpha$$, $$\beta$$ are roots of $${x^2} + x + 1 = 0$$ (given)

But $$\omega$$, $$\omega$$2 are roots of $${x^2} + x + 1 = 0$$

$$\therefore$$ $$\alpha$$ = $$\omega$$, $$\beta$$ = $$\omega$$2 (say)

$$\therefore$$ $${\alpha ^{19}} + {\beta ^7} = {\omega ^{19}} + {\omega ^{14}} = \omega + {\omega ^2} = - 1$$ [$$\because$$ $${\omega ^3} = 1$$ & $$1 + \omega + {\omega ^2} = 0$$]

$${\alpha ^{19}}\,.\,{\beta ^7} = {\omega ^{19}}\,.\,{\omega ^{14}} = {\omega ^{33}} = 1$$

$$\therefore$$ Required equation is $${x^2} - ( - 1)x + 1 = 0$$

i.e. $${x^2} + x + 1 = 0$$

2

WB JEE 2009

MCQ (Single Correct Answer)

If a, b, c are real, then both the roots of the equation $$(x - b)(x - c) + (x - c)(x - a) + (x - a)(x - b) = 0$$ are always

A
positive
B
negative
C
real
D
imaginary

Explanation

Given equation is

$$(x - b)(x - c) + (x - c)(x - a) + (x - a)(x - b) = 0$$

or, $$3{x^2} - 2(a + b + c)x + ab + bc + ca = 0$$

$$D = {b^2} - 4ac = 4{(a + b + c)^2} - 4\,.\,3(ab + bc + ca)$$

$$ = 4[{a^2} + {b^2} + {c^2} - ab - bc - ca]$$

$$ = 2[{(a - b)^2} + {(b - c)^2} + {(c - a)^2}] \ge 0$$

So roots are real.

3

WB JEE 2009

MCQ (Single Correct Answer)

The quadratic equation whose roots are three times the roots of $$3a{x^2} + 3bx + c = 0$$ is

A
ax2 + 3bx + 3c = 0
B
ax2 + 3bx + c = 0
C
9ax2 + 9bx + c = 0
D
ax2 + bx + 3c = 0

Explanation

$$3a{x^2} + 3bx + c = 0$$

Let roots of given equation are $$\alpha$$, $$\beta$$

$$\therefore$$ $$\alpha + \beta = - {b \over a}$$

$$\alpha \beta = {c \over {3a}}$$

$$\therefore$$ New roots are $$\gamma$$, $$\delta$$ $$\therefore$$ $$\gamma$$ = 3$$\alpha$$, $$\delta$$ = 3$$\beta$$

$$\gamma + \delta = 3(\alpha + \beta ) = - {{3b} \over a}$$

$$\gamma \delta = 3\alpha \,.\,3\beta = {{3c} \over a}$$

$$\therefore$$ Quadratic equation is $${x^2} - (\gamma + \delta )x + \gamma \delta = 0$$

$$ \Rightarrow {x^2} + {{3b} \over a}x + {{3c} \over a} = 0 \Rightarrow a{x^2} + 3bx + 3c = 0$$

4

WB JEE 2009

MCQ (Single Correct Answer)

The sum of all real roots of the equation $$|x - 2{|^2} + |x - 2| - 2 = 0$$ is

A
7
B
4
C
1
D
5

Explanation

$$|x - 2{|^2} + |x - 2| - 2 = 0$$

Let $$|x - 2| = t$$

$$\therefore$$ $${t^2} + t - 2 = 0 \Rightarrow (t + 2)(t - 1) = 0$$

$$\Rightarrow$$ t = $$-$$2 or 1

If t = $$-$$2 then $$|x - 2| = - 2$$, but modulus of any value is non negative, so it has no solution.

If t = 1, then $$|x - 2| = 1 \Rightarrow x - 2 = \pm 1 \Rightarrow x = 3$$ or 1

$$\therefore$$ Sum of roots = 3 + 1 = 4

Joint Entrance Examination

JEE Main JEE Advanced WB JEE

Graduate Aptitude Test in Engineering

GATE CSE GATE ECE GATE EE GATE ME GATE CE GATE PI GATE IN

Medical

NEET

CBSE

Class 12